Clinical effectiveness of the Eruption Guidance Appliances in treating malocclusion in the mixed dentition: A systematic review and meta‐analysis. Issue 6 (5th May 2022) - Huang, Shuying; Chen, Yong; Chen, Tianmu; Mallineni, Sreekanth Kumar; McGrath, Colman; Hagg, Urban
Abstract: Aim: To evaluate the clinical effectiveness of the eruption guidance appliances (EGAs) in treating malocclusion in the early mixed dentition. Design: Electronic databases were comprehensively searched for the eligibility literature of the EGA treatment for a period spanning from the earliest available date in each database up to July 2021. Randomized controlled trials, controlled clinical trials, and prospective and retrospective cohort studies were included in the present review. The quality of clinical trials was assessed according to the Cochrane Collaboration's tools (RoB2.0 and ROBINS‐I), whereas cohort studies were based on the Newcastle‐Ottawa Scale (NOS). The data were gathered and synthesized with the Stata software (version 12). Results: The screen yielded 436 articles, of which 17 papers were potentially eligible, and 7 articles from 3 studies (1 RCT, 1 CCT, and 1 PCS) were qualified for the final review and analysis. The meta‐analysis showed both favorable dentoalveolar and skeletal changes in short term. Both overjet and overbite had a significant decrease after treatment (MD = −2.38 mm, 95% CI: −2.82 to −1.94, p  < .001, and MD = −2.43 mm, 95% CI: −3.52 to −1.35, p  < .001, respectively), and SNB increased significantly by 0.73 degrees (95% CI: 0.17–1.28, p  = .01). After the retention period, however, overbite had a significant increase of 0.88mm, which indicated the occurrence of a relapse (95% CI: 0.60–1.16, p  < .001). Conclusions: According to the existing evidence, the EGA treatment is effectively correcting overjet and overbite in the early mixed dentition in short term; furthermore, high‐quality and long‐term studies are warranted to determine its long‐term effectiveness.